Establishment and application of loop-mediated isothermal amplification coupled with nanoparticle-based lateral flow biosensor (LAMP-LFB) for visual and rapid diagnosis of Candida albicans in clinical samples - Wang, Yu; Zhao, Xue; Zhou, Yuhong; Lu, Jingrun; Yu, Honglan; Li, Shijun (Frontiers in Bioengineering and Biotechnology, 2022)
Candida albicans (C. albicans) is an opportunistic pathogenic yeast that predominantly causes invasive candidiasis. Conventional methods for detecting Candida species are costly, take 3–5 days, and require skilled technicians. Rapid pathogen identification is important in managing invasive candidiasis infection. Here, a novel molecular diagnostic assay termed loop-mediated isothermal amplification combined with nanoparticles-based lateral flow biosensor (LAMP-LFB) was developed for C. albicans rapid detection. A set of six primers was designed based on the C. albicans species-specific internal transcribed spacer 2 (ITS2) gene. The C. albicans-LAMP results were visually reported by LFB within 2 min. Various fungal strains representing Candida species, as well as several Gram-negative and Gram-positive bacterial species, were used to determine the analytical sensitivity and specificity of the assay. The optimal LAMP conditions were 64 °C for 40 min, with a sensitivity of 1 fg of genomic DNA template from C. albicans pure cultures. No cross-reactions were obtained with non-albicans strains. Thus, the analytical specificity of the LAMP-LFB assay was 100%. The entire procedure could be completed within 85 min, including specimen processing (40 min), isothermal reaction (40 min), and result reporting (within 2 min). In 330 clinical samples (including 30 whole blood, 100 middle segment urine, and 200 sputum samples), all C. albicans-positive (62/330) samples were identified by LAMP-LFB assay, and the diagnostic accuracy was 100% when compared to the traditional clinical cultural-based methods. Thus, this assay can be used as a diagnostic tool for the rapid, accurate, sensitive, low-cost and specific detection of C. albicans strains, especially in resource-limited settings.